It is time for a better clip applier – 3 mm, percutaneous, non-crushing and locking. Issue 4 (4th July 2018) - Yuval, Jonathan B.; Weiss, Daniel J.; Paz, Adrian; Bachar, Yehuda; Brodie, Ronit; Shapira, Yinon; Mintz, Yoav
Abstract: Introduction: Since the advent of laparoscopy there have been attempts to minimize abdominal wall incisions. For this purpose smaller instruments have been produced. Our aim was to develop the first 3 mm percutaneous clip applier and to make it better than the standard clips of today. Material and methods: The ClipTip clip is made of Nitinol and has a crocodile shaped jaws, which when apposed effectively seal vessels. The shaft operates as a retractable needle permitting percutaneous insertion. Closing, reopening and reclosing is possible. The physical properties of the device were compared to three commercially available clip appliers. Surgeries were performed on porcine animals by experienced surgeons. Results: In comparison to available clips, the superiority of the ClipTip is a combination of wide effective length alongside the ability to withstand strong forces. In live animal studies the Cliptip was inserted into the peritoneal cavity without any injuries. Vessels were ligated successfully and no clip dislodgement or leakage occurred. Conclusions: We developed the next generation clip applier with better properties. Advantages include its length, the needleoscopic caliber, non-crushing effect, locking mechanism and wide aperture. The device has performed safely and effectively in pre-clinical tests. Further studies are planned in humans.